IDENTIFIKASI RAYAP PERUSAK POHON DI ARBORETUM SYLVA UNIVERSITAS TANJUNGPURA - Sulantika, Sulantika; Diba, Farah (JURNAL HUTAN LESTARI, 2019)
The main destructive wood organism is termites. Trees are attacked by live tree termites and also dead trees. As happened in the Arboretum area of Untan, where many trees were damaged caused by it. The aim of the study was to identify the types of tree destroyers in the Sylva Arboretum area of Untan. This study uses a field survey by exploring all the blocks found in the Untara Sylva Arboretum with an area of 3.2 ha. The results of the study at the Sylva University Arboretum in Tanjungpura from 20 observation blocks were 13 blocks which were attacked and 7 blocks were not exposed to termite attacks. Termites found 3 types of termites, these types include 2 types of soil termites (Nasutitermes Sp and Odontotermes Sp.) And 1 type of subterranean termites (Coptotermes curvignatus). The trees that were attacked in the Untan Arboretum area included 13 species of trees, namely: Acacia mangium, Acacia auriculiformis, Melicope lunu-acenda, Paraserianthes falcataria, Shorea seminis, Shorea pacipila, Shorea sp. Shorea revoluta, Dillenia sp, Gluta renghas, Calophillum inopilum, Nephelium lappaceum, Macarangga pruinosa. The most affected trees are Acacia mangium and Acacia Auriculiformis.Keywords: Tree destroyer termites, Arboretum area